Influence of composition of soilless substrates monitored with Iot sensor nodes on the growth, nutrient and fruit quality of rockmelons (Cucumis melo Var. Cantalupensis) - Che Rus, Ridzwan; Salisu, Monsuru Adekunle; Usaizan, Norhanizan; Mat Nashir, Irdayanti; Yusuff, Oladosu; Sulaiman, Zulkefly; Hammed, Ademola (Agricultural Research Communication Centre, 2023)
Background: Coconut coir dust (CD) is commonly used for growing selected fruit and vegetables. It is a soilless medium with excellent drainage and high-water holding capacity; free from infestations of weeds and pathogens. However, plant growth is adversely affected due to its high salinity, potassium and low pH. Methods: A greenhouse experiment was conducted to investigate the influence of different soilless media on rock melon’s growth, nutrient and fruit quality. Five soilless media were prepared including CD as control. A customised portable IoT system was deployed to monitor and collect relevant real-time agronomic data. Result: Plant height, yield, leaf area, total fresh fruit weight and soluble solids content (sweetness) of rock melon were significantly affected by the growing medium. Among the five media used, the growth and quality characteristics were highest in M2 followed by M3. It was found that a combination of burnt rice husk (BRH) and perlite with CD remarkably improved the growth of fruit quality of rock melon.